Smart medical record management system (SMERMS) / Sonia Sabreina Ahmad - Ahmad, Sonia Sabreina (2017)
There is much larger number of patients in a public medical institution than in the private ones. Unfortunately, the majority of the public medical institutions are using the manual type of management system. This manual system has obvious weaknesses, that it gives load of paper works, manual filing works and data redundancy, apart from requiring lots of space and time to manage the files. Patients need to wait for long hours before getting treatments as the medical staffs need to first locate and retrieve the patient’s medical records and details manually. In contrast with the Smart Medical Record Management System (SMERMS) is an embedded system which combines a web-based type of system with a smart card function. The smart card features include the patient details such as patient’s id, name, telephone number and address. The QR code is printed on the surface of patient smart card to indicate the identity of the patient. The QR code stores the patient’s id. The purpose of this study is to design and develop a patient’s smart card system that integrates with SMERMS. The framework methodology is used for this study. PHP language is used to design this system, whilst the language used for the interface is HTML and CSS. The database used in this system is a PhpMyAdmin. In the preliminary stage, questionnaires are designed to elicit information to help further research in the study. The questionnaire includes the medical staff feedback about the current system used in medical institution, as well as public feedback about the service in local hospitals and clinics. Based on the questionnaire conducted, it is found that the computerized system give a clear advantage over a manual system. Indeed, the service level in local hospitals and clinics in Malaysia is dependent on the current system being used. SMERMS is seen to be able to overcome the problems arising from use of the manual system. Thus, it gives an improvement over the effectiveness and the efficiency of the system. For the future work, the mobile type of SMERMS will enhance the use of the system.